Evaluation of Small-Scale Irrigation Scheme Performance and Proposed Alternative Mitigation for Improved Water Management on Wezeqa and Gatto Irrigation Schemes, Southern, Ethiopia - Yohannes Smeneh Ketsela; Birara Gebeyhu Reta; Amare Tadesse Muche (Advances in Agriculture)
The performance of irrigation schemes in Ethiopia is too low due to a lack of proper system management, water control structure, and strong water user association. This study aimed to assess small-scale irrigation scheme’s performance and proposed alternative mitigation for improved water management. Direct measurement, laboratory analysis, field observation, and stakeholder interviews were used to collect the primary data. The average conveyance efficiency, water surface elevation ratio, canal delivery capacity, adequacy, and equity of the Wezeqa and Gatto irrigation schemes were 86.37% and 75.4%, 55% and 60.3%, 71% and 55.8%, 0.68 and 0.67, and 0.4 and 0.43, respectively. The mean value of application and storage efficiencies of the Wezeqa and Gatto irrigation schemes were 59.8% and 49.4% and 94.3% and 92.2%, respectively. The effectiveness of infrastructure and weir sediment ratio in the Wezeqa irrigation scheme was 24.4% and 78.5%, respectively, and almost all infrastructures in the Gatto irrigation scheme were not functional. To solve the water shortage for both systems, water-harvesting technology was proposed having a net volume of harvesting water during the night storage of 13,093.7 and 15,897.6 m3 for Wezeka and Gatto, respectively. Therefore, adopting water-harvesting technology and establishing strong water user associations are recommended to minimize the water scarcity problem to improve water management and sustainability.